A Comprehensive Review of Erectile Dysfunction in Men with Diabetes - Kamenov, Z. A. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Erectile dysfunction (ED) is more common in men with diabetes (DM). Dependent on the selected population, age, DM type and duration, the prevalence of diabetic ED (DED) varies from 32 to 90%. In 12–30% of men ED is the first sign of diabetes, diagnosed later. Today men with diabetes live longer than ever, and develop more late diabetic complications. Having in mind also the global ageing of the world population all this data suggests an increasing number of men with DED in the future. The main factors playing in the complex pathogenesis of DED are diabetic neuropathy (oxidative stress, polyol pathway, advanced glycation end-products, nerve growth factor deficiency, dysfunction of protein kinase C, tissue remodeling, etc.), macrovascular arterial disease (endothelial dysfunction, abnormal collagen deposition and smooth muscle degeneration, dyslipidemia, arterial hypertension, veno-occlusive dysfunction, etc.), hypogonadism, structural remodeling of the corporeal tissue, psychogenic components and adverse drug reactions. The diagnostic process is based on the results of questionnaires, neurological, vascular (Doppler) and other more rarely used investigations.Because of the complex pathogenesis of DED diabetic men represent a “difficult” treatment group. The difficulties are from the “beginning”, because patients do not talk about their problem spontaneously, and doctors do not ask about it. The treatment of DED should be team work, preferably including also specialists in sexual medicine. Psychological support and counseling of the couple is necessary in most cases. The general measures include implementation of a healthier lifestyle, improved glycemic-, lipids-, and arterial pressure control, and careful re-evaluation of the concomitant medications. The specific treatment includes as first line therapy the inhibitors of phosphodiesterase type 5 (PDE-5) with lesser effectiveness compared to non-DM men. There are rare studies with selected diabetic populations and even less with head-to-head comparisons between the PDE-5 inhibitors. Men with DM have a higher prevalence of hypogonadism. Testosterone replacement therapy should be started in symptomatic men with proven hypogonadism and no contraindications. Vacuum constriction devices and intracavernous or intraurethral applications of vasoactive drugs are the second line therapy. Vascular surgery rarely comes into consideration. The penile implant is the last and effective option in men with severe DED.
Keywords: erectile dysfunction; diabetes; diabetic neuropathy; PDE-5 inhibitor; intracavernosal injection; penile implant